Emerging Infections 10 2016
DOI: 10.1128/9781555819453.ch22
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin-Resistant Plasmodium falciparum Malaria

Abstract: For more than five decades, Southeast Asia (SEA) has been fertile ground for the emergence of drug-resistant Plasmodium falciparum malaria. After generating parasites resistant to chloroquine, sulfadoxine, pyrimethamine, quinine, and mefloquine, this region has now spawned parasites resistant to artemisinins -the world's most potent antimalarial drugs. In areas where artemisinin resistance is prevalent, artemisinin combination therapies (ACTs) -the first-line treatments for malaria -are failing fast. This worr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 78 publications
2
86
0
1
Order By: Relevance
“…Artemisinin-based combination therapies (ACTs) are firstline treatment of uncomplicated Plasmodium falciparum malaria in many African countries, where they show excellent cure rates despite concerns about increasing resistance in Southeast Asia. 1,2 Artemisinin resistance is characterized by delayed parasite clearance and associated with point mutations in the P. falciparum kelch protein gene on chromosome 13 (K13). 1,3 Even though the polymorphisms related to P. falciparum artemisinin resistance in Southeast Asia are not prevalent in sub-Saharan Africa, several (other) K13 coding polymorphisms circulate in African countries.…”
Section: Introductionmentioning
confidence: 99%
“…Artemisinin-based combination therapies (ACTs) are firstline treatment of uncomplicated Plasmodium falciparum malaria in many African countries, where they show excellent cure rates despite concerns about increasing resistance in Southeast Asia. 1,2 Artemisinin resistance is characterized by delayed parasite clearance and associated with point mutations in the P. falciparum kelch protein gene on chromosome 13 (K13). 1,3 Even though the polymorphisms related to P. falciparum artemisinin resistance in Southeast Asia are not prevalent in sub-Saharan Africa, several (other) K13 coding polymorphisms circulate in African countries.…”
Section: Introductionmentioning
confidence: 99%
“…46 The pro-oxidant activity of artemisinin is simply too potent and rapid for wild-type parasites to combat and survive. 47 Clinical studies demonstrated increased ROS production in patients with essential hypertension, renovascular hypertension, malignant hypertension. 48…”
Section: The Role Of Artemisinin: Beneficial or Detrimental?mentioning
confidence: 99%
“…1 Malaria treatment should be curative in order to prevent disease progression, relapse (due to the survival of erythrocytic forms in hepatocytes), malarial transmission, and the development of drug resistance. 2,3 Current treatments are hampered by the emergence of parasites with resistance to antimalarial drugs, such as chloroquine, [4][5][6] leading to the utilization of concomitant drugs to increase antimalarial efficacy, such as quinine (QN) plus doxycycline or tetracycline; however, this requires a 7-day course and is poorly tolerated, due to serious side effects caused as cardiotoxicity and the development of cinchonism syndrome. 6,7 Moreover, the high doses required for i.v.…”
Section: Introductionmentioning
confidence: 99%